In-situ Pair Distribution Function Study of the Growth of Supported Platinum Particles in Zeolite X. Issue 1712 (3rd November 2014) - Gámez, Liliana M.; Resto, Oscar; Martinez-Inesta, Maria M.
ABSTRACT: Platinum particles supported in zeolites are used as catalysts for hydrogenation/ dehydrogenation reactions. In this study in situ high energy synchrotron X-ray diffraction was used to study the Pt particle formation under calcination and reduction conditions using time resolved pair distribution function (PDF). Because these particles grow inside the pores of zeolite X, PDF is able to give insight to unique information at the short and medium interatomic distance range that cannot be readily obtained with other techniques. Among the information obtained are the Pt atom interactions during calcination and the evolvement of the Pt particle sizes and average Pt-Pt distances during reduction.